2017
DOI: 10.1016/j.compositesb.2016.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of thermoplastic composites spot-welded and mechanically fastened joints: A preliminary comparison

Abstract: The in-plane and out-of-plane mechanical behaviour of both ultrasonically spot-welded and mechanically fastened joints was investigated by double-lap shear and pull-through tests, respectively. Spot-welded specimens showed comparable onset failure load and significantly higher joint stiffness compared to mechanical fasteners when carrying shear load. The failure modes and the damage within specimens were analysed after mechanical tests. Intralaminar failure and very limited damage on the out-most ply were foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 23 publications
0
32
1
Order By: Relevance
“…Ultrasonic welding is by nature a spot welding technique, hence the most straightforward upscaling route is sequential welding of consecutive spots resulting in a multi-spot welded (MSW) joint. According to our previous research [5], single-spot welded (SSW) thermoplastic composite joints feature similar shear strength to joints with a single mechanical fastener of comparable size. Consequently, multi-spot sequential welding has the potential to become a composite-friendly and fast-processing plausible alternative to mechanical fastening in thermoplastic composite structures.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ultrasonic welding is by nature a spot welding technique, hence the most straightforward upscaling route is sequential welding of consecutive spots resulting in a multi-spot welded (MSW) joint. According to our previous research [5], single-spot welded (SSW) thermoplastic composite joints feature similar shear strength to joints with a single mechanical fastener of comparable size. Consequently, multi-spot sequential welding has the potential to become a composite-friendly and fast-processing plausible alternative to mechanical fastening in thermoplastic composite structures.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, different research [12] showed a good correlation between weld strength and input weld energy for samples with different surface roughness. Finally, energy-controlled ultrasonic welding was successfully used in our previous research [5] to manufacture SSW joints in CF/PEEK adherends with consistent strength, failure modes and welded surface area. Despite these successful results for energy-controlled welding, it must be noted that the welding energy is not only invested in creating the welded joints but it is also dissipated in the adherends and in the clamping jig [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the in-plane static and dynamic behaviour of composite bolted joints has been thoroughly investigated, e.g. [2][3][4][5][6][7][8][9][10][11], only a few works exist in the experimental characterization of pure out-of-plane behaviour of composite fastened coupons, even under quasi-static tensile mode (pull loading) [12][13][14][15][16][17][18]. These joints, which are commonly referred as pull-through or pull-out joints, represent a very critical connection type in advanced aircraft structures and other transportation vehicles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some additional studies [7,8,[15][16][17][18] experimentally investigated the loaddisplacement response and the failure mechanisms of pull-out fastened configurations. A number of these works adequately commented on the concept of the initial failure load (IFL) [15][16][17], defined as the first load drop or a significant stiffness change in the loaddisplacement curve.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in the composites caused by many attractive advantages in comparison to the widely used thermoset composites. The advantages include such properties as high fracture toughness and ductility, ease of shape forming prior to consolidation, significantly faster and lower cost manufacturing, longer shelf life of raw material [1][2][3]. The thermoplastic prepregs can be stored at normal environmental conditions with infinite shelf life in contrast to thermoset prepregs, whose shelf life is mainly limited.…”
Section: Introductionmentioning
confidence: 99%